Exportações brasileiras de carne suína para os principais destinos: uma análise de persistência aos choques - Xavier, Bruna de Souza (2022)
Brazil is the emerging country that most exports pork today. However, it has not advanced in terms of production and exports, occupying, since 2012, the 4th place in the list of the largest producers and exporters of the protein in the world. The main objective of this work is to analyze Brazilian pork exports to the main destinations (China, Russia, Hong Kong, Singapore, Vietnam, Japan and Angola) through an analysis of persistence of shocks between the years 2000 and 2022. The specific objectives are to identify the behavior of each of these series, confirm whether or not they have long memory and verify if the presence of a structural break in the data changes the results of the series. The methodology is based on the long-range dependence test by Lo et al. (1991), and as a way of comparison, other tests were performed, among them are the Classical R/S statistic developed by Hurst (1951); estimation of the fractional integration parameter by spectral regression, or log-perio-dogram, by Geweke and Porter-Hudak (1983); the semiparametric log-periodogram estimator, by Robinson (1995). The results showed that the series exhibit a long memory property and that, in the face of an exogenous shock, Brazilian pork is considered a product with a strong presence in the international market, although subject to export volatility and low diversification of buyers, in addi-tion to political and sanitary interferences. Therefore, the hypothesis confirms the existence of per-sistence of shocks considering that after an exogenous shock it is possible to infer that both the volumes exported and the amounts paid for pork by the selected destinations tend to return to the pattern prior to the event. In this way, the present work differs from the previous literature by analy-zing the behavior of the Brazilian pork export series.